Synergistic Effects of Urea, Poultry Manure, and Zeolite on Wheat Growth and Yield - Abdul Khaliq; Muhammad Shehzad; Mahwish Khan Huma; Majid Mahmood Tahir; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Aftab Jamal; Adil Mihoub; Emanuele Radicetti; Roberto Mancinelli (Soil Systems, 2024)
The agricultural sector faces the dual challenge of enhancing crop productivity and mitigating environmental impacts. Optimizing nutrient management is vital for sustainable agriculture, particularly in sloping terrains like the Himalayan region, where damaged soils require restoration. This study explores the synergistic effects of urea, poultry manure, and zeolite on wheat growth and yield in degraded mountainous soils. A total of twelve treatments were implemented in a randomized complete block design, replicated three times. The treatments included a control (T1); urea nitrogen at 120 kg N ha−1 (UN120) (T2); poultry manure (PM) at 120 kg N ha−1 (T3); zeolite-1 (Z1) at 5 t ha−1 (T4); zeolite-2 (Z2) at 5 t ha−1 (T5); UN120 + Z1 (T6); PM + Z1 (T7); UN120 + Z2 (T8); PM + Z2 (T9); ½ UN + ½ PM + Z1 (T10); ½ UN + ½ PM + Z2 (T11); and ½ UN + ½ PM + ½ Z1 + ½ Z2 (T12). The UN120 treatment demonstrated significant improvements in wheat growth, with notable increases in shoot length (79.7%), shoot fresh weight (50.8%), root length (50.6%), chlorophyll content (53.6%), and leaf area (72.5%) compared to the control. Wheat yield and its components experienced significant improvements when treated with urea nitrogen (UN) and zeolites. Among these treatments, UN120 exhibited the highest efficacy. Nutrient content analysis revealed substantial increases in shoot nitrogen (70.6%), phosphorus (33.3%), and potassium (15.6%) with UN120 treatment compared to the control. The concoction of UN and PM with zeolites further enhanced nutrient levels. Integrating mineral nitrogen sources with organic amendments and zeolites proved effective in enhancing wheat productivity in degraded mountainous soils. Despite positive results, further research is essential for widespread recommendations.